Utilization of Corncob and Tea Waste as Charcoal Briq - T.Anwar Faiz; Lukman Adlin Harahap; Saipul Bahri Daulay (Jurnal Rekayasa Pangan dan Pertanian, 2016)
Briquette is one of the biomass fuels which is used as a simple, inexpensive alternative energy source. Biomass used in this research were corncob and tea waste. The aim of this research was to find out the composition of Bio-Carbon Briquette processing from corncob and tea waste and to determine the best Bio one. Testing was conducted by using a non-factorial completely randomized design with parameters of water content, density, calorific value, and ash content. The results of this research showed that the composition of the briquette materials had highly significant effect on water content, density, calorific value, and ash content. The best water content in this research was 2.89% that met Japanese, American, British and Indonesian standards. The Density value was 0.415 g/cm3 which did not meet briquettes of Japanese, America, British and Indonesian standards. The best calorific value in this research was 10052.08 cal/g that met Japanese, American, British and Indonesian standards. The best ash content value in this research was 2.83% that met Japanese, American, British and Indonesian standards. Keywords : briquette, biomass, corncob and tea waste.